Contributing factors of teenage pregnancy among pregnant teenagers at selected hospitals of Dhaulagiri zone - Chalise, S; Bajracharya, S (Journal of Chitwan Medical College, 2017)
Teenage pregnancy is a challenging issue and public health concern for families, health workers, societies, governments and adolescents themselves both in developed and developing countries. A descriptive study was conducted to find out contributing factors of teenage pregnancy among the pregnant teenagers at selected hospitals of Dhaulagiri zone. Fifty pregnant teenagers attending these hospitals for antenatal check-up and delivery were selected by using non- probability purposive sampling technique. Data were collected by semi structured interview schedule and analyzed and interpreted using descriptive statistics. The finding of this study revealed that 48% respondents were 18 years old, 98% were Hindu, 78% were homemaker, and 15% had positive history of teenage pregnancy in family either-side. Regarding contributing factors of teenage pregnancy, 76% had lower secondary level of education, 92% were living in rural areas, 34% and 58% respectively had no knowledge about its consequences and disadvantage, 14% had faced problem in getting contraceptive of own choice, 94% had cultural acceptance for early marriage and in 58% guardians were less strict in trying to monitor activity were contributing factors of teenage pregnancy. Based on the findings, it is concluded that most of the identified factors were modifiable. For minimizing the teenage pregnancy, chances for girls in formal education should be increased, vocational training should be provided to those not continuing their education, and parents need to be equipped with knowledge regarding teenage pregnancy.